Spiritual Leadership dan Employee Engagement Terhadap Produktivitas SDM Syariah - Sunarto, Sunarto; Marlina, Leni; Misnah; Urbac, Juliyani; Wangge, Trivonia Dona Lau; Febriyanto (Indo-MathEdu Intellectuals Journal, 2026)
Human resource (HR) productivity in sharia-based organizations is a crucial aspect in enhancing organizational effectiveness and competitiveness. However, increased productivity is influenced not only by technical competence but also by leadership factors based on spiritual values ​​and employee engagement to the organization. This study aims to analyze the role of spiritual leadership and employee engagement in improving HR productivity in sharia-based organizations. This study used a library research method with a qualitative approach. Research data were obtained through a review of various relevant literature, such as scientific articles, books, and other academic sources that discuss spiritual leadership, employee engagement, and HR productivity from a sharia perspective. Data were analyzed using content analysis techniques through the stages of identification, grouping, interpretation, and synthesis of various literature findings. The results of the study indicate that spiritual leadership plays a role in building employee values, motivation, and commitment through leadership oriented towards meaning, ethics, and spiritual values. In addition, employee engagement is a crucial factor in driving involvement, loyalty, and increased work productivity. Thus, the integration of spiritual leadership and employee engagement can be a strategy for sharia-based organizations in developing productive and sustainable HR.